Sequential biochar systems: synergies in carbon recycling - Wurzer, Christian (The University of Edinburgh, 2022)
Carbon dioxide removal technologies present an opportunity to alleviate some of the worst consequences of climate change by actively removing CO2 from the atmosphere while the decarbonization of our economies progresses. Biomass valorization through the production of biochar is a unique carbon negative technology as it comprises benefits beyond carbon sequestration, from the utilization of agricultural waste, the co-production of renewable energy to the use as an adsorbent. However, widespread adoption of biochar is still lacking due to economic obstacles in monetizing its various environmental benefits and high production prices compared to fossil materials. I address these obstacles by evaluating current biochar systems and developing an alternative concept to increase the economic competitiveness of biochar. I argue that the price of biochar can be significantly reduced by changing the perception of biochar as a product. Utilization systems specifically designed to monetize biochar’s multifunctional properties are capable to reduce its price without requiring lower production costs. The developed concept of sequential biochar systems is based on the perception of biochar as a carrier for environmental services rather than a product. Within this service-oriented concept, biochar is rented out and recycled rather than sold, enabling an iterative valorization of its properties while retaining its carbon sequestration value. This approach centers around the novel concept of biochar recycling to effectively decouple the price of biochar from its production costs by distributing these costs over several applications. To evaluate the prospects of sequential biochar systems, I conducted an experimental proof-of-concept trial assessing a sequence of three applications connected by two recycling steps. Engineered biochars were designed with a parallel focus on increased application capacity and recycling performance to provide synergies throughout the sequence. The applications targeted the use of biochar in wastewater and gas filtration as high value applications with emerging use scenarios for biochar. Recycled biochars showed comparable performance to commercial materials, and recycling displayed environmental advantages to current methods by retaining carbon throughout the sequence. The exploratory work in this thesis provides various starting points for further research on effective biochar utilization strategies, which are urgently needed to accelerate the development of biochar into an economically self-sustaining carbon dioxide removal technology.
Keywords: biochar; recycling; carbon sequestration; pyrolysis; Water Treatment